Influence of Product Quality, Brand Credibility, and Perceived Value on Customer Satisfaction of MS Glow Users in Bengkulu - Sari, Pera Sunita; Anggarawati, Sularsih (Student Journal of Business and Management, 2024)
Market competition in the cosmetics industry especially skincare is currently increasingly tighter. MS Glow, which was initially the best-selling brand on e-commerce was forced to be replaced by another skincare brand. The inconsistency in MS Glow's sales levels is thought to be because MS Glow is unable to meet consumer satisfaction with the result of using MS Glow products. This is what underlies this research, namely to find out the causes of consumer dissatisfaction with MS Glow products using three variables, namely Product Quality, Brand Credibility and Perceived Value. The method used in this research is a survey method with a sampling technique used a purposive sampling method. The data obtained will be processed by SPSS. The results of research show that the three variables, namely Product Quality, Brand Credibility and Perceived Value, have a positive influence on consumen satisfaction as users of product MS Glow in Bengkulu.